Collective Self-Reliance — A development strategy of promise? - Alfons Lemper (Intereconomics, 1977)
Collective Self-Reliance is the descriptive term for a development strategy which has lately often been suggested as a means of overcoming underdevelopment. The question for us is whether it is to be treated as more than a slogan, which it is still today, and whether it really offers a possible way, a practicable strategy to cope with this global problem. The article by Dr Lemper is followed by another contribution by Professor Bauer concerning this subject.
Keywords: 330; Development Policy